Implementation of the Habit of Reciting the Qur'an Before Learning in Forming Students' Religious Character - Anisa Nur Agustin; Desti Tri Andhini; Hanna Theresia Panjaitan; Linda Apriyani; Nia Maidila; Salsabila Kaila Hujimaki; Novinda Rinjani; Hanna Putri Indriyani; Ratna Dewi (Global Education Journal, 2026)
The strengthening of students’ religious character has become an important concern in elementary education as schools are expected not only to develop cognitive competence but also moral and spiritual values. This study aims to analyze the implementation of the habit of reciting the Qur’an before learning activities in forming students’ religious character at SDN Kedaleman IV. The research employed a qualitative descriptive approach to explore the implementation process and its influence on students’ behavior and learning readiness. The research subjects consisted of Islamic Religious Education teachers and students who participate in the recitation activity, while the object of the study focused on the implementation of Qur’anic recitation as a habituation program in the school environment. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that the recitation activity, conducted routinely from Tuesday to Friday before learning begins, contributes positively to the development of students’ religious character, including improved discipline, emotional readiness for learning, confidence in reading the Qur’an, and a more conducive classroom atmosphere. However, challenges remain, particularly differences in students’ reading abilities and limitations of supporting learning facilities. Overall, the study concludes that the habituation of Qur’anic recitation serves as an effective strategy for integrating religious values into daily school culture.